Perancangan Aplikasi Mobile Tiket Bioskop Dengan Menggunakan Model Diagram Unified Modeling Language (UML) - Setyani, Cicilya; Nur Fadillah, Nahda; Krisda Yanti Halawa, Erlis; Niqotaini, Zatin (LPPM ITB AAS Indonesia, 2025)
Digital transformation in various industries, including the entertainment industry such as movie theaters, has been driven by the advances in information technology. The purpose of this design is to create a mobile application for booking movie tickets using the mobile application that uses an Object-Oriented Analysis and Design (OOAD) approach and models a structured system using Unified Modeling. (OOAD) approach and model the structured system using the Unified Modeling Language (UML). Functionality, interaction flow, and system structure are described in UML diagrams . In designing the User Interface design we used Figma tool. This study found a system that can facilitate the purchase of movie tickets digitally and help managers manage movies more efficiently. The research shows that the approach used is useful for document system requirements and behavior in a visual and systematic way.